2013
DOI: 10.1007/s11664-013-2706-9
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Sn Whisker Growth by Small Bi Additions

Abstract: In this study, the morphological development of electroplated matte Sn and Sn-xBi (x = 0.5 wt.%, 1.0 wt.%, 2.0 wt.%) film surfaces was investigated under diverse testing conditions: 1-year room-temperature storage, high temperature and humidity (HTH), mechanical loading by indentation, and thermal cycling. These small Bi additions prevented Sn whisker formation; no whisker growth was observed on any Sn-xBi surface during either the room-temperature storage or HTH testing. In the indentation loading and thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…The increasing temperature and the alloying element both reduce the length and slow down the whiskers' growth. This result is in agreement with a study which stated that alloying with Fe and Bi on Sn-0.7Cu and ageing at high temperature result in fewer and shorter Sn whiskers [36].…”
Section: Figuresupporting
confidence: 93%
“…The increasing temperature and the alloying element both reduce the length and slow down the whiskers' growth. This result is in agreement with a study which stated that alloying with Fe and Bi on Sn-0.7Cu and ageing at high temperature result in fewer and shorter Sn whiskers [36].…”
Section: Figuresupporting
confidence: 93%
“…However, these theories fail to explain why whiskers eventually still form when a Ni sublayer is used. Other studies on whisker mitigation methods involving Bi or In were reported very recently [23][24][25].…”
Section: Introductionmentioning
confidence: 99%